La réception française de Cicéron au 20e siècle : le cas Carcopino - The French Reception of Cicero in the XX century: the Case of Carcopino - Pià-Comella, Jordi (Ciceroniana On Line, 2020)
Published in 1947, Jérôme Carcopino’s Secrets of Cicero’s Correspondence has provoked violent reactions because of its decidedly negative portrayal of Cicero. This article seeks to understand how one of France’s most brilliant Latinist ended up penning such a prejudiced and unfair portrait of Cicero. Leaning on Carcopino’s biography of Caesar and his autobiography, we argue that this portrait stems from a specific understanding of the figure of the providential man: the au- thor contrasts his Cicero, seen as the symbol of a static republic, with the image of the “great men” such as Caesar, Napoleon, Pétain. In truth, Carcopino manipulates his quotes in the manner of a lawyer, cutting and distorting citations from the Letters. For this former Vichy minister judged and deposed, does his Secrets stage a trial which never took place – the trial against those members of parliament and of the resistance who, in his view, stood out for their opportunism and cowardice?